QA Programme of the TLD laboratory of the University of Costa Rica: IEC 61066 testing - Mora Rodríguez, Patricia (2008)
The Thermoluminescence Personal Dosimetry Laboratory of the University of Costa Rica provides dose measurements for around 90% of occupational radiation workers in the country. The assessment of doses to workers routinely exposed to external sources of radiation constitutes an integral part of any radiation protection programme and helps national authorities to ensure acceptably safe and satisfactory radiological conditions in workplaces. Harshaw Readers Model 4000 and 4500, dosimeter holders Type 8814 with TLD-100 in 0110 cards and loose TLD-100 chips are used to monitor personal dose equivalent, Hp(10) and Hp(0.07). In order to provide a reliable measurement of the operational quantities, a study was undertaken to verify the fulfillment of international requirements in our system (Model 4500 with cards) against the Thermoluminescence dosimetry systems for personal and environmental monitoring CEI IEC 61066 (1991 -2012). The type tests performed were nine in total: batch homogeneity, reproducibility, linearity, detection threshold, effect of climate conditions on reader, effect of light exposure on dosimeters, isotropy, transient voltage and dropping on dosimeters. A Cesium-137 source was used to irradiate the dosimeters and all procedures follow the indications given on the standard. Results showed that all IEC criteria were met by our Laboratory. Acceptable uncertainties were also studied under the ICRP recommendations; the analysis of the Trumpet Curve was done with satisfactory results (for doses above 0.5 mSv; quotient of measure to real dose less than 3%). For purposes of accreditation (ISO/IEC 17025:2005) and performance testing this work is very relevant since the University of Costa Rica wants to establish a solid individual monitoring programme for external radiation exposure that will provide users, registrants, licensees and regulatory bodies with information that can be used for the optimization of protection and dose limitation of Costa Rican workers